CHANGES IN SCHOOL ANXIETY AND EMOTIONAL SELF-REGULATION OF AN ADOLESCENCE EXPERIMENTAL GROUP FOLLOWING THE ABKT-B PROGRAMME - Kalnciema, Baiba; Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this study was to adapt the experimental programme MBCT-C (Randy J. Semple & Jennifer Lee’s programme “Mindfulness-Based Cognitive Therapy for Anxious Children”, 2011) in early adolescents and compare the changes in school anxiety and emotional regulation indicators before and after in the experimental and control group. The necessity for intervention with respect to school anxiety and emotional regulation among children with emotional regulation and school anxiety issues in the early adolescence group was indicated by research into problems connected with youth behaviour and difficulties in regulating emotions. The study analysed the results of six 6th grade students (12-13 years old) using the following instruments: The Emotion Questionnaire (Rydell, Berlin, & Bohlin, 2003, adapted by Grīvza, Brūdere-Ruska, & Raikova, 2014); the School Anxiety Questionnaire (Beeman N. Phillips, 1970, translated by Zalcmane, 2004), the Parent Evaluation Questionnaire (Semple & Lee, 2011) and the Children Evaluation Questionnaire (Semple & Lee, 2011) that have been used in research as assessment instruments. Testing was performed in two stages: before intervention and after 12 intervention sessions. The experimental group showed an improvement in all school anxiety results compared to the control group, but the school anxiety results of control group pupils deteriorated. Emotional regulation indicators for both groups decreased, but the main impact of the experiment was demonstrating that after 12 intervention sessions the level of school anxiety dropped, while scores related to emotional awareness compared to the control group increased.